CAPABILITY OF BACTERIAL METHANOL EXTRACT OF SEAWEED Eucheuma cottonii GROWN ON BACTERIA Escherichia coli FOR IN VITRO - Siti Nursubadriah; Dessy Yoswaty; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was held from 1 to 31 August 2015. The samples were collected from Pasir Panjang coast of Karimun Island of Riau Islans Province. The seaweed Eucheuma cottonii is one of the marine commodities that has high economic value and as a source of non-oil income. seaweed contained organic materials such as polysaccharides, hormones, vitamins, minerals and bioactive compounds. Escherichia coli can cause digestive tract disease such as cholera, typhoid, dysentery, diarrhea and worm diseases. The aim of this study was to analyze differences of antibacterial activity of E. cottonii seaweed extract on the growth of E. coli bacteria. Inhibitory ability seaweed extract that is classified by obtaining the average value in the range of 6-8 mm. Antibacterial activity of E. cottonii seaweed extract tends to be bacteriostatic with an average value of 7.08 diameter with the highest obstacle in the extract concentration of 100%. The results showed that the extract of seaweed E. cottonii has the ability to inhibit the activity of E. coli bacterial growth. Kata kunci: E. cottonii. antibacterial, E. coli, extract, Karimun Island.